Corporate social responsibility of pharmaceutical industry in Korea - Bae, Green; Ahn, Jeong-Hoon; Lim, Kyung-Min; Bae, SeungJin (Frontiers in Pharmacology, 2022)
Background Global pharmaceutical companies in Korea argued that the development of innovative drugs should be recognized as social contribution, yet it has been countered by various stakeholders and the need of distinguish between philanthropic activities and Corporate Social Responsibility (CSR) of pharmaceutical companies and reaching consensus in the Korean context has been raised. We sought to evaluate the CSR status of Korean pharmaceutical companies and collect stakeholders’ opinions to define philanthropic activities and CSR related to pharmaceutical companies in Korea. Methods We conducted literature review on the definition of CSR of pharmaceutical companies, and the CSR activities of the domestic pharmaceutical companies were compared with those of global pharmaceutical companies operating in Korea. The opinions of stakeholder groups (patient advocate groups, consumer organization, domestic/Global pharmaceutical companies) were collected using focus group interviews (FGI) and written surveys. Results Literature review suggested that CSR being categorized as “must do” (economic and legal responsibilities), “ought to do” (ethical responsibilities), and “can do” (philanthropic responsibilities) where contributions beyond the economic, legal, or ethical responsibilities can be defined as “can do” (philanthropic responsibilities). Domestic pharmaceutical companies had just adopted systems for ethical and ESG (Environmental, Social, and Governance) management, which are the 'ought to do' level (ethical responsibility) whereas the headquarter of global pharmaceutical companies had established CSR team and systematically reported on the CSR activity including ESG management reports, which is at the 'ought to do' level and further to the “can do” level, but the Korean branch rarely have CSR teams and the CSR activities in Korea were also insufficient. At the FGI, the global pharmaceutical companies argued CSR activities such as innovational drug development should be recognized as same value with philanthropic activities, yet stakeholders besides them suggested that those activities being “ can do” rather than being philanthropic. Discussion We found that the pharmaceutical companies in Korea are trying to achieve the “ought to do” level (ethical responsibilities) while complying with the “must do” level (legal and economic responsibilities), yet not philanthropic activities. The social consensus regarding philanthropic responsibilities of pharmaceutical companies in Korea were not reached.